Socio-Demographic Determinants as Predictors of Elementary School Pupils Social Competences in Kosovo i Metohija - Kompirović, Tatjana (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The goal of this research is to investigate the differences in social competences of pupils in relation to certain socio-demographic characteristics (gender, academic success, parental educational background, parental employment status, birth order, and hometown). The research, conducted in the period of March-May 2015, involves 705 7th and 8th grade pupils from the territory of Kosovo and Metohija. The assessments of pupils` social competences in school were carried out by the class teachers (N=47). The Scale of Social Behavior in School (Social Competence Subscale) was applied in the research. The obtained results indicate that social competences of the pupils vary in relation to the selected socio-demographic variables. Accordingly, we found statistically significant relations between the gender, academic success, hometown, and educational background of parents. Regarding the dependence between social competences, parental employment status and birth order, no significant differences were found. The obtained results are partly accordant with some previous research.